Kinerja Pasar Ditinjau Dari Good Corporate Governance Dan Sustainability Reporting - Rahman, Nita; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (Gorontalo Accounting Journal, 2024)
This study aims to determine the effect of good corporate governance and sustainability reporting on market performance in general insurance companies that have published stock movements and companies that have been listed on the Indonesia Stock Exchange for the period 2019-2023. The population of this study was 76 companies with certain criteria, the sample in this study was taken using purposive sampling with a sample size of 8 (eight) companies. The data analyzed using Smart PLS (Partial Least Square). The results of the study show that Good corporate governance and Sustainability reporting have an influence on market performance. However, the board of director indicator does not have an influence on insurance market performance.